PHRASAL VERBS IN TAYLOR SWIFT’S 1989 SONG LYRICS AS AUTHENTIC MATERIALS FOR EFL VOCABULARY LEARNING - Wulandari, Maria; Yuliana, Valisa; SM, Syafrianto (Kantor Pelatihan Bahasa dan Budaya, Universitas Atma Jaya Yogyakarta. Gedung Santo Alfonsus, Jl. Mrican Baru No.28, Mrican, Caturtunggal, Kec. Depok, Kabupaten Sleman, Daerah Istimewa Yogyakarta 55281 Phone: (0274) 514319 Email: kpbb@uajy.ac.id, 2025)
Song lyrics are widely recognized as authentic materials that expose EFL learners to natural language use. One linguistic feature that often challenges learners is phrasal verbs, which frequently appear in everyday communication yet are difficult to interpret due to their semantic complexity. This study aims to analyze phrasal verbs in the song lyrics of Taylor Swift's album 1989. Specifically, the study identifies various types of phrasal verbs and their meanings in context. Using content analysis, phrasal verbs found in four selected songs were identified and analyzed in terms of their syntactic characteristics and contextual meanings. The results show that phrasal verbs in the lyrics are used not only as grammatical constructions but also as expressive resources to represent emotional states, interpersonal conflict, and relational dynamics. These uses show that song lyrics can support learners in understanding phrasal verbs through meaningful contextual use. Therefore, the study highlights the pedagogical potential of popular song lyrics as authentic materials for facilitating EFL vocabulary learning, particularly in helping learners comprehend and use phrasal verbs more naturally. Keywords: authentic materials, EFL, phrasal verbs, song lyrics, vocabulary learning